Lean practices transfer in developed countries: a practical case in an electrical wires and cables company - das Neves Almeida, Matheus; Carvalho da Silva, Francimara; Kovaleski, João Luiz; da Conceição Pereira, Pedro Filipe; Carvalho Lima, Bentha Beatriz (International Journal for Innovation Education and Research, 2019)
Although Lean knowledge is widely spread worldwide bringing forth benefits to organizations, observable in the literature is that small-sized enterprises in developed countries do not usually apply this industrial management technique. Therefore, this article has sought to demonstrate that Lean Knowledge Transfer, through the university-enterprise cooperation, may reach expressive results in a wires and cables company. To achieve that, a product family largely impacting the production process has been selected in that company. Next, the tool Value Stream Mapping (VSM) has been used to visualize the current state and, in partnership with the company’s managers, idealize a future state of the process. With that, wastes have been found in the production process and Lean tools have been pointed out to reach improvements proposed in the future state. The results have shown a significant reduction in wastes of: movement of operators (50 and 40% in distances traveled), inventories (44 and 22% of copper), lead time (60 and 53% of the time) and the number of operators (39% in total). Thus, the conclusion is that these results corroborate the literature, where one may apply Lean knowledge transfer in different-sized enterprises so as to seek the reduction of wastes and improve the production process efficiently with the cooperation of universities.